2022
DOI: 10.1186/s12974-022-02398-x
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 signaling in reactive astrocytes counteracts neuroinflammation and ameliorates neuronal damage after traumatic brain injury

Abstract: Background Tissue damage and cellular destruction are the major events in traumatic brain injury (TBI), which trigger sterile neuroimmune and neuroinflammatory responses in the brain. While appropriate acute and transient neuroimmune and neuroinflammatory responses facilitate the repair and adaptation of injured brain tissues, prolonged and excessive neuroimmune and neuroinflammatory responses exacerbate brain damage. The mechanisms that control the intensity and duration of neuroimmune and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 103 publications
0
21
0
Order By: Relevance
“…Also, recent studies reported that EGCs would display inhibitory effects on the proliferation and activity of CD8+ T cells (Kermarrec et al, 2016 ). Though the mechanism underlying such crosstalk between EGCs and CD8+ T cells remains to be fully elucidated, it has been suggested that EGCs may express the checkpoint blockage protein such as PD-L1, similar to that observed in astrocytes of the central nervous system (Gao et al, 2022 ). In addition, it appears a possibility that EGCs might influence the B cell-mediated immunity, as EGCs are present in Peyer’s patches (Biskou et al, 2022 ).…”
Section: Immune Functions Of Egcsmentioning
confidence: 83%
“…Also, recent studies reported that EGCs would display inhibitory effects on the proliferation and activity of CD8+ T cells (Kermarrec et al, 2016 ). Though the mechanism underlying such crosstalk between EGCs and CD8+ T cells remains to be fully elucidated, it has been suggested that EGCs may express the checkpoint blockage protein such as PD-L1, similar to that observed in astrocytes of the central nervous system (Gao et al, 2022 ). In addition, it appears a possibility that EGCs might influence the B cell-mediated immunity, as EGCs are present in Peyer’s patches (Biskou et al, 2022 ).…”
Section: Immune Functions Of Egcsmentioning
confidence: 83%
“…Accordingly, Lipp et al showed an upregulation of PD-L1 on hippocampal astrocytes in a model of axonal degeneration ( 76 ), suggesting a potential role in the inhibition of T cells. Gao et al described the formation of dense areas of activated astrocytes expressing PD-L1 near the lesions in a traumatic brain injury model ( 42 ). In this model, astrocytes acted as gatekeepers, by blocking the infiltration of inflammatory Ly6c hi monocytes/macrophages, but not the entrance of tissue repairing Ly6c low F4/80 ( 42 ) cells.…”
Section: Pd-1 Role During Neuroinflammationmentioning
confidence: 99%
“…Gao et al described the formation of dense areas of activated astrocytes expressing PD-L1 near the lesions in a traumatic brain injury model ( 42 ). In this model, astrocytes acted as gatekeepers, by blocking the infiltration of inflammatory Ly6c hi monocytes/macrophages, but not the entrance of tissue repairing Ly6c low F4/80 ( 42 ) cells.…”
Section: Pd-1 Role During Neuroinflammationmentioning
confidence: 99%
“…Since astrocytes are highly responsive to immune stimuli, they have the ability to upregulate a wide array of chemokines and adhesion molecules that can serve as an immunologic barrier to prevent excessive influx of inflammatory cells during a CNS insult (Figure 2). 120,123 Interestingly, in the event immune cells breach the BBB, enter the perivascular space, and cross astrocyte endfeet into the parenchyma, astrocytes can express immune checkpoint molecules, or inhibitory receptors, which can induce exhaustion and death of leukocytes, 124,125 providing the CNS multiple layers of immunologic protection. As an example, astrocytes are known to upregulate the immune checkpoint protein programmed death ligand 1 (PD‐L1) in response to inflammatory cytokines, primarily interferons 126 .…”
Section: Astrocytesmentioning
confidence: 99%